Two-dimensional amorphous / crystal manganese dioxide material, preparation method thereof, battery positive electrode material and aqueous zinc ion battery

By preparing two-dimensional amorphous/crystalline manganese dioxide materials under ice water bath conditions, the problems of harsh preparation conditions and insufficient performance of manganese oxide positive electrode materials are solved, and high-performance applications of aqueous zinc ion batteries are realized.

CN120573756APending Publication Date: 2025-09-02PETROCHINA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410211561.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-26
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

The existing lithium-ion batteries are limited in the field of large-scale energy storage. The preparation conditions of manganese oxide positive electrode materials are harsh, the cost is high, the specific surface area is low, the electron and ion conduction performance is poor, and there is little research on amorphous MnO2 in aqueous zinc ion batteries.

Method used

Manganate disproportionation reaction under ice water bath conditions is used to generate manganese dioxide, and amorphous/crystalline manganese dioxide material is combined with a reducing agent to generate amorphous/crystalline manganese dioxide material, and the reaction temperature and pH value are controlled to prepare two-dimensional amorphous/crystalline manganese dioxide material with thin thickness and large specific surface area.

Benefits of technology

The rate performance, specific capacity and cycle stability of aqueous zinc ion batteries have been improved. The specific capacity of the material reaches more than 293mAh/g, and the capacity retention rate reaches more than 90% after 100 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120573756A_ABST
    Figure CN120573756A_ABST
Patent Text Reader

Abstract

The invention provides a two-dimensional amorphous / crystal manganese dioxide material, a preparation method thereof, a battery positive electrode material and an aqueous zinc ion battery. The preparation method comprises the following steps: carrying out first reaction on a manganate solution under an ice-water bath condition to obtain a first reaction product; and adding a reducing agent into the first reaction product, carrying out a second reaction under an ice-water bath condition, and washing and drying a product of the second reaction to obtain the two-dimensional amorphous / crystal manganese dioxide material. The invention also provides the two-dimensional amorphous / crystal manganese dioxide material obtained by the preparation method, a battery positive electrode material containing the two-dimensional amorphous / crystal manganese dioxide material, and an aqueous zinc ion battery containing the battery positive electrode material. The two-dimensional amorphous / crystal manganese dioxide material is small in thickness, has a relatively high specific surface area, has amorphous and crystal states at the same time, and is beneficial to improving the electric rate performance, the specific capacity and the cycling stability of the battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zinc ion batteries, and in particular to a two-dimensional amorphous / crystalline manganese dioxide material and a preparation method thereof, a battery positive electrode material and an aqueous zinc ion battery. Background Art

[0002] Large-scale energy storage systems offer advantages such as large capacity, unrestricted site availability, and relatively low energy density requirements, while placing high demands on battery cost and lifespan. While lithium-ion batteries offer numerous advantages, their limited reserves, uneven distribution, and high price limit their application in low-cost, large-scale energy storage systems such as smart grids. Therefore, alongside the development of lithium-ion batteries, there is an urgent need to develop new secondary battery systems with high capacity, long lifespan, and low lifespan costs to meet the growing demand for large-scale energy storage.

[0003] With the advantages of low redox potential, high hydrogen evolution overpotential and high theoretical specific capacity of metallic zinc, the theoretical cost of aqueous zinc ion batteries (ZIBs) is much lower than that of existing lithium ion batteries. They have good application prospects in the field of high-safety large-scale energy storage and are an important development direction for future energy storage. The development of ZIBs is mainly restricted by the research on positive electrode materials. How to find a positive electrode material with suitable microstructure, excellent electrochemical performance and good stability to adapt to Zn with a large ionic radius (and hydrated ionic radius) 2+ The intercalation and deintercalation of manganese oxides (MnO2) have made this research direction extremely urgent. Among them, manganese oxides with variable valence states have demonstrated high capacity and high voltage in aqueous ZIBs. However, drawbacks such as low specific surface area, poor electronic and ionic conductivity, and easy dissolution of electrode materials in the electrolyte during cycling have limited their application in aqueous ZIBs.

[0004] Existing MnO2 electrode materials are basically modified and studied based on various types of crystalline MnO2, and the developed materials have the following problems:

[0005] 1. The preparation conditions are harsh, the multi-step reaction method is complicated, the cost is high, and it is not conducive to industrial production;

[0006] 2. The two-dimensional nanosheet material is relatively thick, the sample uniformity is poor, and the preparation conditions are cumbersome; if the thickness of the nanosheet is to be reduced, a template needs to be added, and the preparation method is more complicated, which is not conducive to large-scale production.

[0007] Currently, there are few reports on the research of amorphous MnO2 in aqueous zinc ion batteries. Therefore, it is necessary to provide an aqueous zinc ion battery electrode material containing amorphous manganese dioxide. Summary of the Invention

[0008] To address the above-mentioned problems, the present invention provides a two-dimensional amorphous / crystalline manganese dioxide material, a preparation method thereof, an aqueous zinc ion battery positive electrode material, and an aqueous zinc ion battery. The two-dimensional amorphous / crystalline manganese dioxide material has a small thickness, a high specific surface area, and possesses both amorphous and crystalline states, which is beneficial for improving the rate performance, specific capacity, and cycle stability of the battery positive electrode material.

[0009] To achieve the above objectives, the present invention provides a method for preparing a two-dimensional amorphous / crystalline manganese dioxide material. The preparation method comprises: subjecting a solution of a manganate to a first reaction in an ice-water bath to obtain a product of the first reaction; adding a reducing agent to the first reaction product; subjecting the product of the first reaction to a second reaction in an ice-water bath; and washing and drying the product of the second reaction to obtain a two-dimensional amorphous / crystalline manganese dioxide material.

[0010] In the above preparation method, the first reaction of the manganate can be a disproportionation reaction, and the manganate generates manganese dioxide and potassium permanganate through the disproportionation reaction. By controlling the first reaction temperature to an ice water bath, the generated manganese dioxide can be crystallized; in the second reaction, the potassium permanganate is reduced by a reducing agent to generate amorphous manganese dioxide, and the amorphous manganese dioxide is combined with the crystalline manganese dioxide to generate a two-dimensional amorphous / crystalline oxide heterojunction material.

[0011] In the above preparation method, the first reaction is carried out in an ice-water bath. By controlling the temperature of the first reaction, the manganese dioxide generated by the disproportionation of the manganate is allowed sufficient time to crystallize, thereby promoting the formation of crystalline manganese dioxide. In some specific embodiments, the temperature of the first reaction is 0°C to 4°C; the first reaction time is 1 hour to 4 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, and other specific values, as well as ranges with any two of the above specific values ​​as endpoints.

[0012] In the above preparation method, in the first reaction, the ice-water bath can be a reaction environment formed by an ice-water mixture.

[0013] In the above preparation method, the manganate may include potassium manganate and / or sodium manganate; correspondingly, the permanganate may include potassium permanganate. In some specific embodiments, the two-dimensional amorphous / crystalline manganese dioxide material prepared using potassium manganate and sodium manganate as raw materials contains potassium ions and sodium ions. The potassium ions and sodium ions can increase the interlayer spacing between the manganese dioxide sheets, which is beneficial for improving the zinc storage capacity of the material.

[0014] In the above preparation method, the concentration of the manganate solution can be controlled to be 0.02mol / L-0.05mol / L, specifically 0.02mol / L, 0.03mol / L, 0.04mol / L, 0.05mol / L and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0015] In some specific embodiments, the solution of the manganate is generally an acidic solution. Specifically, the pH value of the manganate can be 5.5-6.5, specifically 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5 and other specific values, as well as ranges with any two of the above specific values ​​as endpoints.

[0016] In the above preparation method, the temperature of the second reaction is 0°C to 4°C.

[0017] In the above preparation method, the time of the second reaction is 6h-12h, for example, it can be specific values ​​such as 6h, 7h, 8h, 9h, 10h, 11h, 12h, and a range with any two of the above specific values ​​as endpoints.

[0018] In the above preparation method, in the second reaction, the ice-water bath can be a reaction environment formed by an ice-water mixture.

[0019] In the above preparation method, by controlling the reaction temperature and solution pH value of the second reaction, the reaction rate of the second reaction can be controlled to promote the formation of amorphous manganese dioxide.

[0020] In the above preparation method, the reducing agent includes a divalent manganese salt, and may further include a soluble salt of divalent manganese.

[0021] In the above preparation method, the reducing agent includes one or a combination of two or more of MnSO4, MnCl2 and Mn(NO3)2.

[0022] In the above preparation method, the molar ratio of the reducing agent to the manganate is 3-3.3:2.

[0023] According to a specific embodiment of the present invention, the preparation method may further include post-processing the product of the second reaction. The post-processing may include centrifuging the product of the second reaction, washing and drying the precipitate obtained by centrifugation, and obtaining a two-dimensional amorphous / crystalline manganese dioxide material.

[0024] According to a specific embodiment of the present invention, the preparation method of the above-mentioned two-dimensional amorphous / crystalline manganese dioxide material may specifically include:

[0025] 1. Adjusting the pH value of a solution of manganate having a concentration of 0.02 mol / L-0.05 mol / L to 5.5-6.5, and then performing a first reaction in an ice-water bath (0-4° C.) while stirring. The reaction time can be controlled to be 1 h-4 h to obtain a first reaction product, which includes potassium permanganate and crystalline manganese dioxide;

[0026] 2. Maintaining ice-water bath conditions (0-4° C.), adding a reducing agent to the product of the first reaction at a molar ratio of the reducing agent to the manganate of 3:2, stirring, and conducting a second reaction for 6 h-12 h to obtain a second reaction product; centrifuging the product of the second reaction, washing and drying the precipitate obtained by centrifugation (which may be freeze-dried) to obtain the two-dimensional amorphous / crystalline manganese dioxide material.

[0027] The present invention also provides a two-dimensional amorphous / crystalline manganese dioxide material, which is obtained by the above preparation method.

[0028] In the above-mentioned two-dimensional amorphous / crystalline manganese dioxide material, the two-dimensional amorphous / crystalline manganese dioxide material includes amorphous manganese dioxide and crystalline manganese dioxide, wherein the amorphous manganese dioxide can provide a large number of oxygen vacancy defects, so that the material has faster ion diffusion and better structural stability during charge and discharge, thereby improving the specific capacity and cycle stability of the material. Furthermore, the amorphous manganese dioxide and the crystalline manganese dioxide can form a heterojunction, and the heterojunction structure can have both the mechanical stability of crystalline manganese dioxide and the reactivity of amorphous titanium manganese dioxide, and has a higher ion diffusion rate. Accordingly, the two-dimensional amorphous / crystalline manganese dioxide material has both higher specific capacity and cycle stability.

[0029] According to a specific embodiment of the present invention, the above-mentioned two-dimensional amorphous / crystalline manganese dioxide material can be a two-dimensional nano-sheet structure, and the thickness of the single-layer sheet is relatively thin (even ultra-thin), which can greatly reduce the migration distance of ions and electrons, thereby improving the electrochemical properties of the material. In addition, the thickness of the above-mentioned material is thin, the lateral size is large (the lateral size is the size perpendicular to the thickness direction, such as length and width, etc.), and the specific surface area is large, which can provide more electrolyte accessible points for the reaction of the battery, which is conducive to the battery reaching a state of full power storage. In some specific embodiments, the thickness of the two-dimensional amorphous / crystalline manganese dioxide material can be 0.5nm-2nm, and the lateral size of the two-dimensional amorphous / crystalline manganese dioxide material can be 100nm-500nm.

[0030] The present invention also provides a battery cathode material comprising the above-mentioned two-dimensional amorphous / crystalline manganese dioxide material. In some specific embodiments, the above-mentioned battery cathode material can be used in aqueous zinc-ion batteries.

[0031] The present invention also provides an aqueous zinc-ion battery comprising the aforementioned positive electrode material. Using a positive electrode material comprising a two-dimensional amorphous / crystalline manganese dioxide material to prepare an aqueous zinc-ion battery can improve the battery's rate performance, specific capacity, and cycling stability. In some specific embodiments, the aqueous zinc-ion battery can achieve a specific capacity exceeding 293 mAh / g, with a capacity retention rate exceeding 90% after 100 cycles. Furthermore, the aqueous zinc-ion battery can achieve a specific capacity exceeding 298 mAh / g, with a capacity retention rate exceeding 93% after 100 cycles.

[0032] According to a specific embodiment of the present invention, the preparation method of an aqueous zinc ion battery may include:

[0033] 1. Mixing active material, conductive carbon black, and binder in a solvent to form a positive electrode raw material, coating the positive electrode raw material on a metal copper foil, drying and compacting to obtain a positive electrode material; wherein the active material includes the above-mentioned two-dimensional amorphous / crystalline manganese dioxide material;

[0034] 2. Assemble the above-mentioned positive electrode material, counter electrode, electrolyte and separator to form an aqueous zinc ion battery; wherein the counter electrode includes metallic zinc.

[0035] In the above-mentioned method for preparing an aqueous zinc ion battery, the conductive agent may include conductive carbon black.

[0036] In the above-mentioned method for preparing an aqueous zinc ion battery, the binder may include polyvinylidene fluoride and / or PVDF.

[0037] In the above-mentioned method for preparing an aqueous zinc ion battery, the solvent may include N-methylpyrrolidone.

[0038] In some specific embodiments, the mass ratio of the active material, the conductive agent, and the binder can be controlled to be 7:2:1.

[0039] In the above-mentioned method for preparing an aqueous zinc ion battery, the counter electrode may specifically comprise zinc foil. In some specific embodiments, the zinc foil may be pre-treated by polishing to remove an oxide layer on the surface of the zinc foil.

[0040] In the above-mentioned method for preparing an aqueous zinc ion battery, the electrolyte comprises zinc ions and divalent manganese ions, that is, the electrolyte may include a combination of a zinc salt and a divalent manganese salt, such as a combination of zinc sulfate and manganese sulfate. In some specific embodiments, the electrolyte may be a mixed solution of 3M ZnSO4 and 0.1M MnSO4.

[0041] In the above-mentioned method for preparing an aqueous zinc ion battery, the separator may include a glass fiber separator.

[0042] The beneficial effects of the present invention include:

[0043] 1. The two-dimensional amorphous / crystalline manganese dioxide material provided by the present invention has a thin single layer thickness and a large specific surface area, which can not only reduce the migration distance of ions and electrons and improve the electrochemical performance, but also expose more electrolyte accessible points, which is conducive to enabling the battery to reach a full storage state and improve the material's rate performance.

[0044] 2. The two-dimensional amorphous / crystalline manganese dioxide material provided by the present invention has amorphous manganese dioxide, which can introduce more oxygen vacancy defects, so that the material has a faster ion diffusion rate and better structural stability during the battery charging and discharging process, thereby improving the specific capacity and cycle stability of the material, so that the specific capacity and cycle stability of the material reach a higher level. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1a This is a scanning electron microscope image of the sample in Example 1.

[0046] Figure 1b This is the TEM image of the sample in Example 1.

[0047] Figure 1c This is the AFM image of the sample in Example 1.

[0048] Figure 2 XRD patterns of the samples of Example 1 (Hybrid), Comparative Example 2 (c-MnO2) and Comparative Example 1 (a-MnO2).

[0049] Figure 3 This is a high-resolution transmission micrograph of the sample in Example 1.

[0050] Figure 4 Dark field transmission electron microscope image and element distribution map of the sample in Example 1.

[0051] Figure 5 These are the cycle performance diagrams of the samples of Example 1 (Hybrid), Comparative Example 2 (c-MnO2) and Comparative Example 1 (a-MnO2). DETAILED DESCRIPTION

[0052] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of implementation of the present invention.

[0053] Example 1

[0054] This embodiment provides a two-dimensional amorphous / crystalline manganese dioxide material, the preparation method of which includes:

[0055] 1. Adjust the pH value of the potassium manganate solution to 6, and then carry out a first reaction in an ice-water bath (0-4° C.) while stirring for 2 hours to obtain a first reaction product comprising potassium permanganate and crystalline manganese dioxide;

[0056] 2. Maintaining ice-water bath conditions (0-4°C), add reducing agent manganese sulfate to the first reaction product at a molar ratio of reducing agent to manganate of 3:2, stir, and carry out a second reaction for 6 hours. Centrifuge the second reaction product, wash the precipitate obtained by centrifugation, and freeze-dry to obtain a two-dimensional amorphous / crystalline manganese dioxide material.

[0057] This embodiment also provides an aqueous zinc ion battery, and the preparation method of the battery includes:

[0058] 1. Preparation of positive electrode materials:

[0059] The two-dimensional amorphous / crystalline manganese dioxide material prepared in this example was used as the active material. The active material, conductive carbon black, and binder (polyvinylidene fluoride) were ground uniformly in an agate mortar at a mass ratio of 7:2:1. N-methylpyrrolidone (NMP) was added dropwise and stirred continuously until it became a uniform paste. The paste was applied to copper foil using a spatula, dried under vacuum at 100°C for 12 hours, and compacted on a tablet press (approximately 10 MPa) to obtain the positive electrode material. The positive electrode material was transferred to an argon-filled glove box and placed for more than 6 hours before being assembled.

[0060] 2. Assemble aqueous zinc ion batteries:

[0061] A zinc foil, polished to remove the surface oxide layer, was used as the counter electrode. The counter electrode had a thickness of 0.5 mm and a diameter of 16 mm. The electrolyte was a mixture of 3 M ZnSO₄ and 0.1 M MnSO₄. A Whatman fiberglass separator was used as the separator. The positive electrode material, counter electrode, electrolyte, and separator were assembled in air to produce an aqueous zinc-ion battery. The assembled aqueous zinc-ion battery was aged for 12 hours before testing.

[0062] Example 2

[0063] This embodiment provides a two-dimensional amorphous / crystalline manganese dioxide material, and its preparation method is similar to that of Example 1, except that: in this embodiment, potassium manganate is replaced by sodium manganate. Other experimental conditions are the same, and crystalline / amorphous manganese oxide nanosheets with sodium ions intercalated are obtained.

[0064] This embodiment also provides an aqueous zinc ion battery. The material of the battery is prepared using the two-dimensional amorphous / crystalline manganese dioxide material of this embodiment as raw material. The preparation method of the battery is the same as that of Example 1.

[0065] Comparative Example 1

[0066] This comparative example provides a two-dimensional amorphous manganese dioxide material, the preparation method of which is similar to that of Example 1, except that: in this comparative example, the first reaction is omitted, and a potassium permanganate solution is directly prepared. The amount of potassium permanganate in the potassium permanganate solution and the concentration of potassium permanganate in the solution are the same as the amount of potassium permanganate and the concentration of potassium permanganate in the solution in the first reaction product of Example 1; then, a divalent manganese salt MnSO4 is added to the potassium permanganate solution as a reducing agent, and the ratio of the reducing agent to potassium permanganate is the same as that in Example 1; and a second reaction is carried out according to the conditions of Example 1 to obtain manganese oxide nanosheets with a fully amorphous structure.

[0067] Comparative Example 2

[0068] This comparative example provides a two-dimensional manganese dioxide material, the preparation method of which is similar to that of Example 1, except that:

[0069] In this comparative example, the first reaction and the second reaction temperatures were maintained at room temperature (20-25° C.), and other experimental conditions were the same, and manganese oxide nanosheets with a crystalline structure were obtained.

[0070] Comparative Example 3

[0071] This comparative example provides a two-dimensional manganese dioxide composite material, which is obtained by uniformly mixing the samples obtained in comparative example 1 and comparative example 2 in a mass ratio of 1:1 by mechanical grinding.

[0072] Test Example 1

[0073] This test example provides the structural characterization results of the two-dimensional manganese oxide materials prepared in the above examples and comparative examples.

[0074] Figure 1a The SEM image of the sample of Example 1 shows that the sample has a two-dimensional lamellar structure. The sample of Example 2 is characterized and the sample of Example 2 also has a two-dimensional lamellar structure.

[0075] Figure 1b TEM image of the sample in Example 1, Figure 1c This is the AFM image of the sample in Example 1. Figure 1b 、 Figure 1c It can be seen that the sample of this example has a graphene-like morphology, with irregular flakes, a lateral dimension of 100nm-500nm, and a flake thickness of approximately 0.5nm. Characterization of the sample of Example 2 revealed that the sample of Example 2 has a similar morphology to that of the sample of Example 1, and has a thickness of 0.5-2nm and a lateral dimension of 100nm-500nm.

[0076] Figure 2These are the XRD diagrams of the sample of Example 1 (Hybrid), the sample of Example 2 (c-MnO2) and the sample of Comparative Example 1 (a-MnO2). It can be seen that the sample of Comparative Example 1 is amorphous, the sample of Comparative Example 2 is crystalline, and the crystallinity of the sample of Example 1 is between the crystallinity of the samples of Comparative Example 1 and Comparative Example 2.

[0077] Figure 3 This is a high-resolution TEM of the sample from Example 1. As can be seen from the figure, the sample has crystalline and amorphous regions. Figure 2 The results show that the sample of Example 1 contains crystalline manganese dioxide and amorphous manganese dioxide.

[0078] Figure 4 The dark field transmission electron microscopy image and element distribution map of the sample in Example 1 show that K, Mn, and O are evenly distributed in the sample, and potassium ions are evenly distributed between the manganese dioxide layers.

[0079] Figure 5 The figure shows the cycling performance of the sample in Example 1 (Hybrid), the sample in Example 2 (c-MnO2), and the sample in Comparative Example 1 (a-MnO2). As can be seen from the figure, the sample in Example 1 maintains a high capacity and efficiency during 100 cycles.

[0080] Test Example 2

[0081] This test example provides the electrochemical performance test results of the aqueous zinc ion batteries prepared in the above examples and comparative examples.

[0082] An aqueous zinc ion battery was assembled according to the method of Example 1. The specific capacity and performance after 100 cycles of the battery were tested. Table 1 shows the electrochemical performance of zinc ion batteries assembled with the electrodes prepared above, tested at a current density of 100 mA / g.

[0083] Table 1

[0084]

[0085] The above results indicate that the zinc ion battery provided by the present invention can maintain a 100-cycle cycle stability of more than 90% while achieving a specific capacity of 293 mAh / g.

Claims

1. A method for preparing a two-dimensional amorphous / crystalline manganese dioxide material, the method comprising: The manganate solution is subjected to a first reaction in an ice-water bath to obtain a first reaction product; A reducing agent is added to the first reaction product, and a second reaction is carried out in an ice-water bath. The product of the second reaction is washed and dried to obtain a two-dimensional amorphous / crystalline manganese dioxide material.

2. The preparation method according to claim 1, wherein The temperature of the first reaction is 0°C to 4°C, and the time of the first reaction is 1h-4h; The temperature of the second reaction is 0° C. to 4° C., and the time of the second reaction is 6 h to 12 h.

3. The preparation method according to claim 1, wherein The manganate includes potassium manganate and / or sodium manganate.

4. The preparation method according to claim 1, wherein The reducing agent includes a divalent manganese salt; Preferably, the reducing agent includes one or a combination of two or more of MnSO4, MnCl2 and Mn(NO3)2.

5. The preparation method according to claim 1, wherein The molar ratio of the reducing agent to the manganate is 3-3.3:

2.

6. A two-dimensional amorphous / crystalline manganese dioxide material obtained by the preparation method according to any one of claims 1 to 5.

7. The two-dimensional amorphous / crystalline manganese dioxide material according to claim 6, wherein: The two-dimensional amorphous / crystalline manganese dioxide material includes amorphous manganese dioxide and crystalline manganese dioxide.

8. The two-dimensional amorphous / crystalline manganese dioxide material according to claim 6, wherein: The thickness of the two-dimensional amorphous / crystalline manganese dioxide material is 0.5 nm-2 nm, and the lateral size of the two-dimensional amorphous / crystalline manganese dioxide material is 100 nm-500 nm.

9. A battery positive electrode material, comprising the two-dimensional amorphous / crystalline manganese dioxide material according to any one of claims 6 to 8.

10. An aqueous zinc ion battery comprising the battery positive electrode material according to claim 9.

11. The aqueous zinc ion battery according to claim 10, wherein The specific capacity of the aqueous zinc ion battery is above 293 mAh / g, and the capacity retention rate is above 90% after 100 cycles.